PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN ALAT DAN MESIN PERTANIAN ( PTK PADA SISWA KELAS XI PENYULUH PERTANIAN SMK NEGERI 2 WALENRANG ) - Imran Y, Andi Ali; Yahya, Muhammad; Darmawang, Darmawang (Universitas Negeri Makassar, 2017)
This thesis is based on the results of a classroom action research (Classroom Action Research) aims to determine the implementation of cooperative learning model jigsaw to improve student achievement in the subject of tools and agricultural machinery. The research subject is class XI student of Agricultural Extension SMK Negeri 2 Walenrang totaly 30 people. The results showed that the application of cooperative learning model jigsaw implemented, the test cycle I obtained an average score of 66.4 and the second cycle tests obtained an average score of 75.83. The results of this study obtained a description that by using a model of cooperative learning jigsaw can streamline the learning. This is indicated by an increase in the frequency of attendance of students, the courage to ask and answer questions in the learning process, presenting result of discussions in front of the class, and punctuality in collecting duties and the increasing seriousness of the students in the following subjects agricultural tools and machines